P219 Evaluating medical thoracoscopy services at a District General Hospital over the past 13 years. (14th November 2013) - George, LM; Roberts, HJ; Downer, NJ; Cox, GM; Ali, NJ; Roberts, ME
Abstract : Introduction: Medical thoracoscopy is an invaluable tool in the management of undiagnosed and known malignant pleural effusions. In the UK, increasing numbers of centres are offering the procedure We present the experience from a single district general hospital that has been offering medical thoracoscopy over the last 13 years. Methodology: A retrospective analysis of 411 case notes of patients who had a medical thoracoscopy between July 2000 and April 2013. Results: 291 patients (71%) were male. The median age was 70 years (24 to 92). In 321 patients (78%) the procedure was done for diagnostic purposes and the procedure was done on the right side (20%) had lung cancer, 94 (23%) had mesothelioma and 66 ( 16%) had other cancer. In the 231 patients that had operator observations as appearing malignant 198( 86%) were confirmed on histology. 34 ( 30%) patients had malignancy in operator observations that were reported as inflammation but reassuringly no patients had malignancy in the operator observations that were reported as appearing normal. Talc poudrage was done in 261 ( 64%)patients. 53 patients (13%) required a further pleural intervention within 12 months. Complications included empyema in 3 (0.7%), renal failure in 6 (1.4%) and trapped lung in 20 (5%) patients. 6 patients (1.4%) died within 15 days of the procedure and major contributors to mortality were hospital acquired infection. Conclusions: Medical thoracoscopy is an effective procedure for diagnosing and managing pleural effusions. It is associated with a low complication rate and can be performed in patients with poor performance status. Caution should be exercised in patients with multiple comorbidities and careful management of cardiovascular status post-operatively could help reduce post-procedure kidney injury.